2017
DOI: 10.1515/ract-2016-2690
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation properties of radiation shielding materials such as granite and marble against γ-ray energies between 80 and 1350 keV

Abstract: AbstractIn this study, the γ-ray energy-dependent mass and linear attenuation coefficients of various granite and Turkish marble species have been experimentally obtained. Radionuclides (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…4 shows that the values of HVL for the present G1-G6 glasses increased with the increments in the incident photon energy. It is found that the HVL thickness is the lowest for G6 glass system with ρ=6.22 g/cm 3 and the highest for G1 glass system with ρ=5.82 g/cm 3 . It can be easily expressed that the HVL values reduces with the increase of density; hence the shielding superiority increases with the density of the material.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…4 shows that the values of HVL for the present G1-G6 glasses increased with the increments in the incident photon energy. It is found that the HVL thickness is the lowest for G6 glass system with ρ=6.22 g/cm 3 and the highest for G1 glass system with ρ=5.82 g/cm 3 . It can be easily expressed that the HVL values reduces with the increase of density; hence the shielding superiority increases with the density of the material.…”
Section: Resultsmentioning
confidence: 91%
“…In order to determine the characteristic of the selected glass systems and the possibility of development as a promising shielding material, it is required to compare the radiation shielding performance with previously published various materials (such as concretes, glasses [42]. The obtained HVLs have lower than all concretes (C1-C7) and glasses (S1-S7) while they are higher than those of Gl4, Gl5 and Gl6 glass samples having densities of 7.726, 7.801 and 8.284 g/cm 3 , respectively [39]. Furthermore, the present results are a rather similar as those of Gl2 and Gl3 glass types.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Roughly speaking, photons and particles with energies above about 10 electron volts (eV) are ionizing (some authorities use 33 eV, the ionization energy for water). Particle radiation from radioactive material or cosmic rays almost invariably carries enough energy to be ionizing [5].…”
Section: Introductionmentioning
confidence: 99%
“…Various Turkish granites and marble spices were investigated via measuring (µ), (µ/ρ) the half value layer and the tenth value layer, at the energy region 80.99 keV to 1.332 MeV using HPGe detector, the results were compared with literature. [10] The density of hydrous peridotite magma containing 5% wt. H2O was measured at pressures and temperatures up to 4.3 GPa and 2073-degree K, respectively, using the X-ray absorption method.…”
Section: Introductionmentioning
confidence: 99%